Supraventricular Tachycardia as the Initial Presentation of New-Onset Lupus: A Case Report. Issue 9 (18th September 2021) - Rayburn, David; Gerke, Steven
Abstract: Systemic lupus erythematosus (SLE) is a chronic, autoimmune, multisystem disorder that can sometimes be life-threatening. The presentation varies widely given the wide range of clinical and serological manifestations coupled with the disease's ability to affect any organ. Prognosis depends on the organ systems involved, as well as the severity of the involvement. This case involves a 17-year-old with initial presentation of supraventricular tachycardia subsequently found to have pancreatitis, myocarditis, and nephritis secondary to a new diagnosis of SLE. Systemic lupus erythematosus can involve virtually any organ system, which leads to the variable nature of presentation, as was the case for our patient and his presentation being supraventricular tachycardia from underlying myocarditis secondary to SLE. Lupus myocarditis is rare, but when present often indicates severe systemic illness. The echocardiogram will often show global hypokinesis without evidence of coronary artery disease. This was the case with our patient. His echocardiogram demonstrated new-onset systolic left-sided heart failure due to nonischemic cardiomyopathy with an ejection fraction of 25%. Unfortunately for our patient, he had several poor prognostic factors on his initial presentation prior to any treatment being started, including renal disease, male, age (17 years), low socioeconomic status, African American race, and high disease activity. Systemic lupus erythematosus is the great mimicker and can present in a variety of ways. Given its ability to involve virtually any organ system, it is important to consider it on the differential diagnoses, especially in patients with a strong family history.